ChemInform Abstract: Ascorbic Acid as an Initiator for the Direct C—H Arylation of (Hetero)arenes with Anilines Nitrosated in situ. Issue 32 (24th July 2014) - Crisostomo, Fernando Pinacho; Martin, Tomas; Carrillo, Romen
Abstract: Ascorbic acid is successfully applied in this reaction as a radical initiator.